Western Balkans EU Accession: Is the 2025 Target Date Realistic? - Richard Grieveson; Julia Grübler; Mario Holzner (The Vienna Institute for International Economic Studies (wiiw), 2018)
The European Commission has set a target date of 2025 for Western Balkan EU accession, while also outlining a broader new strategy which includes Brussels taking a more active role in solving political disputes in the region, and upgrading infrastructure as part of the Berlin Process. We welcome these moves economic underdevelopment in the region is closely tied to political fractures. Aside from resolving political conflicts, improved governance in the region will also be necessary. In terms of meeting economic accession criteria, the region faces a host of challenges, but we believe that a focus on upgrading infrastructure and developing a much bigger and more competitive industrial base should be the priorities. While the economic influence of third parties in the region is not as significant as often portrayed, this is not guaranteed to last, particularly in the case of China, which is set to increase its economic presence in the Western Balkans in the coming years. Even if the region takes a great leap forward towards the EU, there are other barriers in the way which could also hold back accession. Nevertheless, while the 2025 target represents a highly ambitious best-case scenario, it could serve as a powerful incentive for countries in the region to speed up their reform agendas. We do not completely rule out at least Montenegro and Serbia joining the bloc by 2025 or shortly thereafter.
Keywords: E60; F15; F21; F43; H54; O11; O14; O18; O20; O24; 330; integration; governance; economic growth; competitiveness; industrialisation; infrastructure; economic policy; Western Balkans; EU